Perianal Basal Cell Carcinoma Successfully Managed with Excisional Biopsy - Paola C. Aldana; Harris G. Yfantis; Preeti R. John (Case Reports in Dermatological Medicine)
Basal cell carcinoma (BCC) is the most common cutaneous malignancy in the United States and is often nonaggressive. Its location in the perianal region is very rare and it is estimated that only 0.08% of all BCCs occur in this region. Herein, we present a case of perianal basal cell carcinoma, nodular type. The diagnosis was made using excisional biopsy of a skin lesion. Immunohistochemical staining confirmed the diagnosis: it showed diffuse and strong positivity for smooth muscle actin (SMA) and monoclonal antibody BER-Ep4 and was negative for carcinoembryonic antigen (CEA), pancytokeratin (AE1/AE3), and epithelial membrane antigen (EMA). The treatment of choice has traditionally been local excision to clear margins but the newest guidelines recommend Mohs Micrographic surgery (MMS) or standard 4mm surgical margins for this high-risk BCC. Our patient was successfully treated using excisional biopsy without recurrence. In select patients with lesions smaller than 1cm, excisional biopsy may be sufficient to treat the disease and may be better tolerated than MMS and wider surgical margins. Literature review suggests a predisposition for perianal BCC in individuals susceptible to cutaneous malignancies. Therefore, any history of cutaneous malignancy should further prompt clinicians to examine nonsun exposed areas on full body skin exams.